Single nucleotide polymorphisms in a gene for translation initiation factor (eIF4G) of rice (Oryza sativa) associated with resistance to Rice tungro spherical virus - Lee, Jong-Hee; Muhsin, Muhammad; Atienza, Genelou A.; Kwak, Do-Yeon; Kim, Suk-Man; De Leon, Teresa B.; Angeles, Enrique R.; Coloquio, Edgardo; Kondoh, Hiroaki; Satoh, Kouji; Cabunagan, Rogelio C.; Cabauatan, Pepito Q.; et al. (Scientific Societies, 2010)
Rice tungro disease (RTD) is a serious constraint to rice production in South and Southeast Asia. RTD is caused by Rice tungro spherical virus (RTSV) and Rice tungro bacilliform virus. Rice cv. Utri Merah is resistant to RTSV. To identify the gene or genes involved in RTSV resistance, the association of genotypic and phenotypic variations for RTSV resistance was examined in backcross populations derived from Utri Merah and rice germplasm with known RTSV resistance. Genetic analysis revealed that resistance to RTSV in Utri Merah was controlled by a single recessive gene (tsv1) mapped within an approximately 200-kb region between 22.05 and 22.25 Mb of chromosome 7. A gene for putative translation initiation factor 4G (eIF4Gtsv1) was found in the tsv1 region. Comparison of eIF4Gtsv1 gene sequences among susceptible and resistant plants suggested the association of RTSV resistance with one of the single nucleotide polymorphism (SNP) sites found in exon 9 of the gene. Examination of the SNP site in the eIF4Gtsv1 gene among various rice plants resistant and susceptible to RTSV corroborated the association of SNP or deletions in codons for Val1060-1061 of the predicted eIF4Gtsv1 with RTSV resistance in rice.